Unveiling DENND2D as a Novel Prognostic Biomarker for Prostate Cancer Recurrence: From Gene to Prognosis - Chi-Fen Chang; Lih-Chyang Chen; Yei-Tsung Chen; Chao-Yuan Huang; Chia-Cheng Yu; Victor C. Lin; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Biomedicines)
Background: Prostate cancer is a major global health burden, with biochemical recurrence (BCR) following radical prostatectomy affecting 20–40% of patients and posing significant challenges to prognosis and treatment. Emerging evidence suggests a critical role for differentially expressed in normal and neoplastic cell (DENN) domain-containing genes in oncogenesis; however, their implications in prostate cancer and BCR risk remain underexplored. Methods: This study systematically evaluated 151 single-nucleotide polymorphisms in DENN domain-containing genes in 458 patients with prostate cancer and BCR, followed by validation in an independent cohort of 185 patients. Results: Multivariate Cox regression analyses identified DENND2D rs610261 G>A as significantly associated with improved BCR-free survival in both cohorts (adjusted hazard ratio = 0.39, 95% confidence interval = 0.23–0.66, p = 0.001). Functional analysis revealed rs610261’s regulatory potential, with the protective A allele correlating with increased DENND2D expression in various human tissues. Compared to normal prostate tissues, DENND2D expression was reduced in prostate cancer, with higher expression being linked to favorable patient prognosis (p = 0.03). Gene set enrichment analysis revealed an association between DENND2D expression and the negative regulation of MYC target genes, including MAD2L1, ERH, and CLNS1A, which are overexpressed in prostate cancer and associated with poor survival. Furthermore, the elevated DENND2D expression promotes immune infiltration in prostate cancer, supporting its role in immune modulation. Conclusions: DENND2D is a prognostic biomarker for BCR in prostate cancer and offers new avenues for personalized treatment strategies.